Extraction of kaempferol from Wattakaka volubilis and evaluation of its protective effects against aluminium-induced liver toxicity - Usharani Saminathan; Anuradha Ramamoorthy; Ambiga Somasundaram; Sivasankari Sekar; Sivagurunathan Paramasivam; Pasiyappazham Ramasamy (Phytomedicine Plus)
Introduction: The goal of this study was to find out if kaempferol, a compound isolated from the Wattakaka volubilis plant, could protect the liver of rats that were given aluminum sulfate. Methods: Kaempferol, a bioflavonoid, was isolated from the leaves of W. volubilis methanolic extract (MEWV) and characterized by using the High-performance thin-layer chromatography (HPTLC)technique. The liver protective activities of MEWV against aluminum poisoning were investigated in male albino rats, as their protective efficacy was assessed in addition to that of the silymarin standard. The oral administration of silymarin (25 mg/kg), kaempferol (10 mg/kg), and MEWV (200 mg/kg) was administered continuously for 14 days. The body and liver weights as well as serum enzymes like alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were calculated. Results: Advanced techniques successfully isolated and confirmed the bioactive constituent kaempferol from MEWV. When kaempferol and MEWV were given to rats that had been poisoned with aluminum, their body mass index went up significantly (p < 0.001) and the relative weight of their liver and serum marker enzymes went down significantly (p < 0.001) compared to animals that had only been poisoned and analyzed the comparative action of the extract and isolated compound using silymarin, the standard drug. Kaempferol showed better protection against aluminum-induced hepatotoxicity compared to MEWV treatment. Conclusion: In conclusion, the results showed that kaempferol and MEWV reduced the damage done to the liver by aluminum sulfate by protecting cells, the liver, and protecting antioxidants.